2022
DOI: 10.1111/jre.13082
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant crevicular fluid and serum levels of soluble ST2 in peri‐implant diseases: A pilot study

Abstract: Background and Objective Soluble ST2 (sST2) is a current biomarker of cardiovascular disease. It is used to predict susceptibility to cardiovascular diseases and to analyze their prognosis. Serum sST2 level increases in inflammatory diseases such as periodontitis. However, the level of sST2 in peri‐implant diseases and crevicular fluid has not been investigated yet. Thus, the aim of this cross‐sectional study is to analyze the level of sST2 in peri‐implant health and diseases. Methods Sixty‐nine participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(112 reference statements)
1
5
0
Order By: Relevance
“…The findings demonstrated that, in comparison to healthy periodontal conditions, the mean sST2 value in the GCF was significantly greater in periodontal disease patients. These outcomes align with previous research (15,28). Numerous inflammatory and immunological diseases, such as pneumonia, rheumatoid arthritis, diabetes, cancer, cardiovascular events, and periodontitis, are related to sST2 levels (15,(29)(30)(31)(32).…”
Section: Discussionsupporting
confidence: 88%
“…The findings demonstrated that, in comparison to healthy periodontal conditions, the mean sST2 value in the GCF was significantly greater in periodontal disease patients. These outcomes align with previous research (15,28). Numerous inflammatory and immunological diseases, such as pneumonia, rheumatoid arthritis, diabetes, cancer, cardiovascular events, and periodontitis, are related to sST2 levels (15,(29)(30)(31)(32).…”
Section: Discussionsupporting
confidence: 88%
“…Finally, a total of 11 articles were eligible for inclusion in the review, among which seven were case–control studies ( 17 – 23 ), and four were cross-sectional studies ( 24 27 ) ( Table 1 ; Figure 1 ). Five studies ( 17 , 19 , 22 , 25 , 26 ) compared participants with healthy implants. Another four studies only mentioned that participants from comparison groups were with healthy oral conditions ( 18 , 20 , 21 , 24 ) and did not specify whether dental implants existed or not.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 32 blood parameters were measured to investigate the association between peri-implantitis and systemic inflammation ( Supplementary Table 2 ). After the assessment of available data, one study was not eligible to be included in the meta-analysis due to a lack of standard deviation ( 20 ), and another article presented the data only as medians ( 25 ). Finally, nine articles were included in the quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontitis is an infectious‐inflammatory disease of the tooth‐supporting tissues that is mediated by a disrupted immune‐inflammatory response to a pathogenic biofilm (Könönen et al, 2019). Elevated serum levels of sST2 have been associated with periodontitis (Torrungruang et al, 2019), and two pilot studies recently demonstrated increased gingival and peri‐implant crevicular fluid levels of ST2 in periodontitis and peri‐implant diseases, respectively (Navya et al, 2022; Ozgur et al, 2022). However, there is no prior research on salivary sST2 levels of periodontitis patients or, naturally, on the effect of periodontal treatment on salivary sST2 levels.…”
Section: Introductionmentioning
confidence: 99%